I05 Sustained mutant huntingtin lowering in the brain and cerebrospinal fluid of huntington disease minipigs mediated by AAV5-MIHTT gene therapy. (September 2018) - Valls, Astrid; Brouwers, Cynthia; Pintauro, Roberta; Snapper, Jolanda; Bohuslavova, Bozena; Sogorb-Gonzalez, Marina; Fodale, Valentina; Bresciani, Alberto; Ellederova, Zdenka; Blits, Bas; Motlik, Jan; Deventer, Sander van; et al.
Abstract : Background: HTT-lowering therapies hold great promise to slow-down or halt neurodegeneration in Huntington disease (HD). We have developed an engineered microRNA targeting human huntingtin (HTT), delivered via adeno-associated viral vector serotype 5 (AAV5-miHTT), leading to efficient HTT-lowering in vitro and in vivo in rodent models. Aim: To assess the translatability of our approach in a large animal model: transgenic HD (tgHD) minipigs. Methods: Animals were injected with AAV5-miHTT (1.2 × 1013 gc/brain), bilaterally into striatum (caudate and putamen) and sacrificed 6 months post-treatment. Across different brain regions, vector DNA, miHTT and mutant HTT (mHTT) mRNA were measured by Q-PCR, and mHTT protein using an ultrasensitive immunoassay. In longitudinal cerebrospinal fluid (CSF) samples, miHTT and mHTT protein expression were assessed by Q-PCR and ultrasensitive immunoassay, respectively. Results: Widespread brain biodistribution of vector DNA was observed, with the highest levels in target (striatal) regions but also in thalamus and cortical regions, in both grey and white matter. Expression of miHTT was highly correlated with vector DNA in all brain areas. Corresponding to the vector DNA and miHTT expression, a reduction of mHTT mRNA and protein was observed in AAV5-miHTT treated animals with respect to controls. mHTT protein lowering was on average more than 75% in the injected areas, and between 30–50% in most of the distal regions. Translational pharmacokinetic and pharmacodynamic measures in the CSF were in line with the effects observed in the brain. We detected CSF miHTT, and CSF mHTT protein lowering up to 50% at 3 and 70% at 6 months post-dosing. Conclusions: This study demonstrates widespread biodistribution and durable efficiency of AAV5-miHTT in disease-relevant regions in a large brain, and the potential of CSF translational measures to follow-up efficacy.